Моделювання впливу фізичного навантаження на зміну функціонального стану людини - Лукаш, С.І.; Будник, М.М. (Комп’ютерні засоби, мережі та системи, 2014)
The simulation model of reaction of the systems of human organism is offered under the action of loading for realization of diagnostics of human on the method of Ruffier-Dickson. The state of the cardiovascular system is determined.